Qualidade de vida relacionada à saúde, atividade física e uso de drogas lícitas por adolescentes do ensino médio de Tocantinópolis(TO). - Sousa, Raylane Carneiro de (Universidade Federal do Tocantins, 2020)
Introduction:Adolescence is a period in which various transformations and identity formation occur, making adolescents vulnerable to risk situations, such as the use of licit drugs, specifically alcohol and cigarettes, which can impair health-related quality of life. Objective:To verify the association between health-related quality of life, physical activity and licit drug use by high school adolescents from Tocantinópolis (TO). Methods:This is a cross-sectional quantitative study conducted with 162 adolescents from 14 to 19 years old. A questionnaire wasapplied by interview, with sociodemographic information, time of physical activity, cigarette and alcohol use, health-related quality of life, assessed by KIDSCREEN -27, Body Mass Index and sedentary behavior. In the data analysis, the information was entered in Excel 97 -2003 and analyzed in the Stata 13 statistical program, adopting a significance level lower than 5% (p <0.05). Results:The practice of physical activity was associated with the general health-related quality of life score in the domainsphysical well-being and the social support domain and peer group among students who reported not smoking. Among those who reported not consuming alcohol, physical activity was associated with the general health-related quality of life score in the physical well-being domain. Conclusion:Physically active adolescents, who do not drink alcohol and do not smoke, had better health-related quality of life, in the domains physical well-being, social support and peer group.